Skilled migrants in Andalusia: occupational segregation and overqualification (2005-2023) - Montero-González, Bárbara; Camacho-Ballesta, José A.; Bretones, Francisco D. (Revista de Estudios Andaluces, 2025)
This article analyses the occupational segregation of highly qualified immigrants working in Andalusia, comparing their situation with that of native workers and migrants with different educational levels. Ordered probability models are employed to identify the most influential variables affecting the occupational position of this group, with a particular focus on factors such as education, language, and job stability. Drawing on microdata from the Labour Force Survey for the period 2005–2023, which spans various economic cycles, the findings reveal that investment in education significantly enhances the labour market position of immigrants. Nevertheless, approximately 30% of highly qualified immigrants in Andalusia experience overqualification, indicating that the Andalusian labour market is not fully capitalising on the potential of this group.